Testing a Self-Determination Theory Model of Healthy Eating in a South African Township - De Man, Jeroen; Wouters, Edwin; Delobelle, Peter; Puoane, Thandi; Daivadanam, Meena; Absetz, Pilvikki; Remmen, Roy; van Olmen, Josefien (Frontiers in Psychology, 2020)
Introduction The burden of type 2 diabetes is growing rapidly in sub-Saharan Africa. Healthy eating has been shown to prevent the disease but is challenging to maintain. Self-determination theory offers a motivational framework for maintaining a healthy diet based on evidence from western settings. This study aims to assess whether self-determination theory can explain healthy diet behavior in a disadvantaged urban South African population. Methods Cross-sectional data from a South African township population (N = 585; pre-diabetes = 292, diabetes = 293, age 30-75) were analyzed using structural equation modelling, while controlling for socio-demographic factors. Measures included self-reported autonomous and controlled motivation, perceived competence (measured through barrier self-efficacy), perceived relatedness (measured through perceived participation of significant others) and, as indicator for healthy diet, frequency of fruit, vegetable and non-refined starch intake. Results Healthy eating was positively associated (β = 0.26) with autonomous motivation, and negatively associated (β = -0.09) with controlled motivation. Perceived competence and relatedness were positively associated with healthy eating (β = 0.49 and 0.37) and autonomous motivation (β = 0.65 and 0.35), and negatively associated with controlled motivation (β = -0.26 and -0.15). Autonomous motivation mediated the effect of perceived competence and relatedness on healthy eating. The model supported a negative association between controlled and autonomous motivation. Conclusion This is the first study providing evidence for self-determination theory explaining healthy eating in a disadvantaged sub-Saharan African setting among people at risk of or with diabetes type two. Our findings suggest that individuals who experience support from friends or family and who feel competent in adopting a healthy diet are more likely to become more motivated through identifying the health benefits of healthy eating as their goal. This type of autonomous motivation was associated with a healthier diet compared to individuals whose motivation originated in pressure from others or feelings of guilt or shame. Our recommendations for public health interventions include: focus on the promotion of diet-related health benefits people can identify with; encourage social support by friends or family; reinforce people’s sense of competence and skills; and avoid triggering perceived social pressure or feelings of guilt.